Comparison of Doppler back-scattering and charge exchange measurements of E × B plasma rotation in the DIII-D tokamak under varying torque conditions. (1st September 2022) - Pratt, Q; Rhodes, T; Chrystal, C; Carter, T
Abstract: Measurements of the E × B toroidal angular velocity, ω E × B = E r / R B θ ( E r is the radial electric field, B θ is the poloidal magnetic field), are made using the Doppler back-scattering (DBS) and charge-exchange recombination (CER) spectroscopy diagnostics. DBS uses the Doppler shift of wavenumber-resolved density fluctuations while CER uses the Doppler shift of impurity emission lines to independently measure plasma parameters for calculating the local radial electric field. DBS and CER profiles of ω E × B as a function of normalized toroidal flux ( ρ ) are compared at various levels of neutral beam applied torque on the plasma. Under standard neoclassical theory ω E × B is a flux surface quantity, making it appropriate to compare across diagnostics. DBS and CER generally show good agreement when comparing ω E × B profiles at different levels of neutral beam injection-applied torque. Furthermore, the DBS values have close to the same precision as CER values when averaged over a similar time-scale and effects, such as prompt-torque are considered. DBS is able to observe the rapid ( < 10 ms) modification of the E r profile by the diagnostic neutral beam 'blips'. This modification is most pronounced when the blip applies a large relative change in torque on the plasma. Overall, these results could have implications on transport analysis and suggests using DBS and CER in conjunction to constrain values of the E × B -shear (sometimes called γ E × B ).